Tuling Wendan Decoction combined with flunarizine in the treatment of migraine patients and the effect of intervention on serum cyclooxygenase-2, endothelin-1 and nitric oxide - Xie, Xiayang; Shang, Kai; Li, Xuejing (Cellular and Molecular Biology, 2020)
This experiment aimed to explore the curative effect of Tuling Wendan Decoction combined with flunarizine on migraine patients and the intervention effect on serum cyclooxygenase-2 (COX-2), endothelin-1 (ET-1), nitric oxide(NO) levels. For this purpose, from January 2019 to January 2020, 96 patients with migraine in our hospital were selected as the research object. Using a simple randomization method, patients who meet the criteria were assigned 1:1, and each patient was assigned a random number, of which the number 1 to 48 were the observation group, and the number 49 to 96 were the control group. The control group was treated with flunarizine, and the observation group was treated with Tuling Wendan Decoction combined with flunarizine. Comparing the efficacy, incidence of adverse reactions, the incidence of headache, cerebral blood flow rate [basal artery (BA), vertebral artery (VA), middle cerebral artery (MCA)], vascular endothelial function (serum COX-2, ET-1, NO levels), neurological function [5-hydroxytryptamine (5-HT), brain-derived neurotrophic factor (BDNF), calcitonin gene-related peptide (CGRP)] before treatment, 4 weeks and 8 weeks after treatment between the two groups. The results for efficacy showed that after 8 weeks of treatment, the total effective rate of the observation group (93.75%) was higher than that of the control group (77.08%, P<0.05). In regards to the situation of headache attack, the number of headache attacks, duration, pain degree and accompanying symptom scores of the observation group after 4 weeks and 8 weeks of treatment were lower than those of the control group (P<0.05). Results of cerebral blood flow velocity showed that the blood flow velocity of BA, VA, MCA in the observation group was lower than that in the control group after 4 and 8 weeks of treatment (P<0.05). Vascular endothelial function results indicated that the serum COX-2 and ET-1 levels of the observation group were lower than those of the control group after 4 weeks and 8 weeks of treatment, and the serum NO levels were higher than that of the control group (P<0.05). The serum BDNF and CGRP levels of the observation group were lower than those of the control group after 4 weeks and 8 weeks of treatment, and the serum 5-HT levels were higher than the control group (P<0.05). The incidence of adverse reactions between the two groups was not statistically significant (P>0.05). It was concluded that Tuling Wendan Decoction combined with flunarizine is the first treatment for migraine, with definite curative effect and can effectively improve the onset of headache, reduce the speed of cerebral blood flow, regulate vascular endothelial function and nerve function, and ensure safety.